SPECIFIC FEATURES OF SYNONYMS IN SAIDA ZUNNUNOVA'S POEMS - Khujamberdiyeva Guzalkhon Zafarjon qizi (Bright Mind Publishing, 2026)
In this article, the synonyms used in the poems of Saida Zunnunova features are discussed. The phenomenon of language units have the same meaning is called synonymy. A group of mutually synonymous words is called a line of synonymy. One word in a set of synonyms is the head word. The examples given in the article are from the poems of the poetess Saida Zunnunova.
Keywords: Synonym, ambiguity, expressiveness, synonymous.